Comparison of calculated by DFTB electronic excitation energies of CdS nanosized clusters with DFT results - Aldongarov, A; Assilbekova, A. M.; Irgibaeva, I. S.; Mantel, A. I. (Eurasian Journal of Physics and Functional Materials, 2026)
Nano-dimensional crystalline cadmium sulfide is a semiconductor that exhibits size-dependent opto-electronic properties, determined by the effects of quantum confinement. Due to these effects, it is possible to adjust the optical properties of the final cadmium sulfide clusters by varying their size. In this work we report the results of a theoretical study of CdS nanoparticles with the methods of the density functional tight-binding (DFTB) and the time-dependent density functional theory TD DFT. The calculations of the electronic absorption spectra of CdS crystals were performed on cadmium sulfide nanoparticles with an amount of from 5 to 137 atoms. The DFTB method was used for the structural optimization of the studied nanoparticles. The optimization results showed that the clusters will be a wurtzite structure and the geometrical parameters of the structure are close to the known experimental data for a CdS crystal. For the obtained optimized structures, the electronic absorption spectra were calculated by the linear response methods in the DFTB approximation and the time-dependent density functional theory of the TD-DFT approximation. It is shown that the data obtained by the DFTB method are close to those that can be obtained using DFT calculations for cadmium sulfide clusters. Especially good agreement is obtained when using large clusters with small values of the dipole moment. Recommended Citation Aldongarov, A. A.; Assilbekova, A. M.; Irgibaeva, I. S.; and Mantel, A. I. (2020) "Comparison of calculated by DFTB electronic excitation energies of CdS nanosized clusters with DFT results," Eurasian Journal of Physics and Functional Materials: Vol. 4: No. 3, Article 8. DOI: https://doi.org/10.29317/ejpfm.2020040308